SANDBLASTING PADA KAPAL MV. BERLIAN INDAH - Andi Hendrawan; Lusiani; Rinaldi Aprilian (Saintara: Jurnal Ilmiah Ilmu-Ilmu Maritim, 2020)
Sandblasting is one of the easiest methods to remove rust or dirt such as oil, paint, etc. on the surface or to change the surface character of the material, either to make it coarser or make a surface smoother, generally applied to metal-based surfaces. Sandblasting is done by spraying abrasive material, usually in the form of silica sand or steel grit with relatively high pressure on a surface. The purpose and research is to explain the sanblasting method on MV vessels. Beautiful diamonds. The method used in this study is a descriptive method that explains the phenomena that occur. ship cleaning methods carried out in the framework of ship maintenance. Sandblasting is very much related to the process of painting a ship. almost every work on sandblasting will continue with ship painting.